Indoleamine-2,3-dioxygenase: An important controller in maintaining mesenchymal stem cell-mediated immunomodulatory homeostasis - Yufei Hui; Xue Jiao; Li Yang; Dejin Lu; Yanbo Han; Wen Yang; Yanli Cao; Yuxi Miao; Shiqiang Gong; Minjie Wei (Acta Pharmaceutica Sinica B, 2025)
Mesenchymal stem cells (MSCs) have been widely used in the treatment of various autoimmune and inflammation-related diseases due to their potent immunomodulatory properties. Several studies have demonstrated that MSC-mediated immunomodulation is complex and bidirectional, with the in vivo microenvironment influencing the direction of this modulation. Indoleamine-2,3-dioxygenase (IDO), an immunosuppressive factor, has been identified as a key “switch” in the immunomodulatory role of MSCs. In this review, we explore how IDO functions as a critical regulator of MSC immunoregulatory plasticity. We delve into the mechanisms by which changes in IDO expression affect the function of various immune cells, summarize relevant research and clinical advances regarding the role of IDO expression in MSC-based therapies for various diseases, and discuss potential therapeutic strategies that target IDO to enhance the stability of MSC therapeutic effects. This provides a theoretical foundation for optimizing MSCs as safer and more effective clinical therapeutic agents.